2006
DOI: 10.1007/s10517-006-0431-6
|View full text |Cite
|
Sign up to set email alerts
|

Surface adhesins of lactobacilli loosely connected to the cell wall and eliminated into the environment during culturing in liquid nutrient media

Abstract: Six lactobacillus species and 4 clones of one of them were studied in order to clear out the ratio between the adhesion capacities of concanavalin A-reactive glycoprotein adhesins on the surface of the bacterial cell and glycoprotein adhesins released into the broth during culturing in liquid nutrient media. The adhesive activity of cultures is largely determined by the strain rather than species appurtenance. Elimination of glycoprotein adhesins from the bacterial cell and their antagonistic activity towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The first group is composed of proteins that contain a signal peptide, which is located in the N-terminal part of the sequence to direct the protein to the protein export machinery. The second group includes surface-associated proteins that are simply shed from the bacteria due to the normal turnover of the cell wall (Anokhina et al, 2006b;Turner et al, 2004;Driessen & Nouwen, 2008;Sánchez et al, 2009b). Secretion systems are highly conserved among eubacteria, given the high degree of homology among the genes coding for their monomeric components (van Wely et al, 2001).…”
Section: Proteins Secreted By Probiotic Bacteriamentioning
confidence: 99%
“…The first group is composed of proteins that contain a signal peptide, which is located in the N-terminal part of the sequence to direct the protein to the protein export machinery. The second group includes surface-associated proteins that are simply shed from the bacteria due to the normal turnover of the cell wall (Anokhina et al, 2006b;Turner et al, 2004;Driessen & Nouwen, 2008;Sánchez et al, 2009b). Secretion systems are highly conserved among eubacteria, given the high degree of homology among the genes coding for their monomeric components (van Wely et al, 2001).…”
Section: Proteins Secreted By Probiotic Bacteriamentioning
confidence: 99%
“…Cultures identified as C. albicans in Nickerson chromogenic medium (HiMedia) with parallel induction of the germinative tubule growth in the presence of the serum were selected for the experiment. C. albicans strains for further experiments were cultured in Saburo broth at 37 o C for 24 h [1].…”
Section: Methodsmentioning
confidence: 99%
“…However, after preincubation of these cells with Lactobacillus strains freshly isolated from the vaginas of clinically healthy women, adhesion of C. albicans to the target cells decreases by 30-40%. The use of commercial lactobacterial preparations (acylact or lactobacterin) for the same purpose is little effective, because these preparations are based on strains of enteric origin; being introduced into the vagina, these probiotic lactobacillus cultures (not characteristic of this biotope) almost loose their capacity to adhere to VE and colonize them.We previously showed that L. fermentum strain 90 TS-4 (21) expresses adhesin capable of detaching from the cell surface into the culture medium [1]. The components of the resultant culture fluid (CF) binding to VE membrane receptors compete with adhesins of other bacteria preventing their colonization on the mucosa.…”
mentioning
confidence: 99%
See 2 more Smart Citations